Aspek Hukum Anak Korban Kekerasan Seksual Atas Tindak Pidana Pencabulan Sesama Jenis Yang Dilakukan Orang Dewasa Terhadap Anak Dan Peranan Pemerintah Dalam Perlindungan Anak - Rusmiadi, Panji Caesar; Iman, Candra Hayatul (Peneliti.net, 2024)
Crime is a name or label given by people to assess certain actions, as evil, all forms of treatment that disturb and damage their basic rights in various forms of inhumane use and exploitation which must be stopped immediately without exception. In connection with the problems expressed above, to find out what factors cause criminal acts of same-sex sexual abuse committed by adults who commit obscene acts of the same sex, to find out the legal consequences that will occur for criminal acts of same-sex sexual abuse. , to find out the efforts made by the government, parents and society in dealing with criminal acts of same-sex sexual abuse committed by adults. This research method was carried out using a normative juridical approach. The data used uses primary data, secondary data and tertiary data. The resource persons for this research consisted of investigators from the Criminal Investigation Unit IV for the Protection of Women and Children at the Karawang Police and the Women's Empowerment and Child Protection Service. The data collection procedure in writing this research was by means of literature and field studies. Data analysis uses qualitative analysis. Based on the results of the research and discussion, the factors that cause criminal acts of same-sex child molestation committed by adults against children are factors such as social inequality, lack of supervision from parents, factors such as the presence of sexual disorders. The consequences of children dealing with the law for criminal acts of sexual violence by perpetrators include legal consequences such as legal protection and rehabilitation, there are also non-legal consequences of Betrayal. Sexual Trauma, Feeling Helpless, What efforts can children make as victims and responsibilities of the government, parents, society in protecting children in conflict with the law for victims of criminal acts of sexual violence by adults, protection of children in conflict with the law for criminal acts of sexual violence, which are carried out and the responsibilities carried out by the government in protecting children, namely , Providing rehabilitation efforts both within the institution and outside the institution.